Senegal : Grassroots Democracy in Action - Easton, Peter (World Bank, Washington, DC, 2012)
At a time when the fate of national representative government in Senegal, still hangs in the balance, a variety of grassroots organizations is seemingly, and unexpectedly laying some of the groundwork for future change. Notions of "democracy" - adapted to local Senegalese conditions - are being woven among various assertions of human rights. The note describes how a rural women's non-formal education program, has been developing a brand of local training in democratic principles, and behaviors. Efforts specifically targeted women, and included lessons in problem-solving, income generation, African-language literacy, and child health. However, one such effort was a module on women's health, which included the taboo subject - women's sexuality - triggering an unsuspected emphasis on human rights, particularly as it relates to discrimination, and violence. The surprising results were conducive to surface the term "democracy", laying the foundation for a training sequence where democracy would be used as a cover term for the social arrangements, under which human rights could be guaranteed, and people could determine their own destiny. Results were evident on a number of fronts: children's rights, girl's access to school, and female circumcision, among others. The democracy debate appears to be having major effects on practice, within local associations, and communities, which includes notions of accountability, transparency, and governance.